Putting the pieces together: Integration for forest landscape restoration implementation. (4th December 2019) - Mansourian, Stephanie; Parrotta, John; Balaji, Poorna; Bellwood‐Howard, Imogen; Bhasme, Suhas; Bixler, R. Patrick; Boedhihartono, Agni Klintuni; Carmenta, Rachel; Jedd, Theresa; de Jong, Wil; Lake, Frank K.; Latawiec, Agnieszka; et al.
Abstract: The concept of forest landscape restoration (FLR) is being widely adopted around the globe by governmental, non‐governmental agencies, and the private sector, all of whom see FLR as an approach that contributes to multiple global sustainability goals. Originally, FLR was designed with a clearly integrative dimension across sectors, stakeholders, space and time, and in particular across the natural and social sciences. Yet, in practice, this integration remains a challenge in many FLR efforts. Reflecting this lack of integration are the continued narrow sectoral and disciplinary approaches taken by forest restoration projects, often leading to marginalisation of the most vulnerable populations, including through land dispossessions. This article aims to assess what lessons can be learned from other associated fields of practice for FLR implementation. To do this, 35 scientists came together to review the key literature on these concepts to suggest relevant lessons and guidance for FLR. We explored the following large‐scale land use frameworks or approaches: land sparing/land sharing, the landscape approach, agroecology, and socio‐ecological systems. Also, to explore enabling conditions to promote integrated decision making, we reviewed the literature on understanding stakeholders and their motivations, tenure and property rights, polycentric governance, and integration of traditional and Western knowledge. We propose lessons and guidance for practitioners and policymakers on ways to improve integration in FLR planning and implementation. Our findings highlight the need for a change in decision‐making processes for FLR, better understanding of stakeholder motivations and objectives for FLR, and balancing planning with flexibility to enhance social–ecological resilience.